Fotografia w nurcie teoriopoznawczym - Jakubowicz, Michał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents four programmes of artistic photography related to the reflection on media. The initial part is devoted to the specificity of relationship between photography and the so called pre-media, characterized by perception, that is light, air. The second chapter presents the relationship between photographic grain structure and the uniform field theory which forms the basis of knowledge in the scope of visual composition and creation of signs. Within the third part, the photography is described at the background of the development of digital technology impacting substantially the change of process of picture creation. The final chapter concerns relations between photography and the social media, understood as a specific bond linking people who avail of photographs for communication purposes.